Men's Health : Staying Young Looking Great - Lafavore, Michael, editor 641248 (Emmaus, Pa. : Rodale Press, 1997)
As we plow headlong into the Information Age, men are being bombarded with facts and advice about every imaginable topic. How can men filter this huge amount of information? By reading Men's Health Staying Young, Looking Great. Here you'll discover the most useful knowledge on topics that are important to men, brought to you by top experts in the fields of fitness, sex, food, health, career and grooming.